A Juridical Analysis of Constitutional Court Decision No. 39/PUU-XVIII/2020 on Regulatory Imbalances between Conventional Television Broadcasting and Over-The-Top Media from the Perspective of Justice - Rohayati, Siti Nur; Izomiddin, Izomiddin; Harun, Muhamad (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2025)
The advancement of digital technology has given rise to internet-based Over The Top media services that operate outside the broadcasting regulatory framework governing conventional television as stipulated in Law Number 32 of 2002. This regulatory imbalance creates concerns of injustice, as conventional television broadcasters bear heavier legal obligations compared to digital platforms. The disparity prompted a judicial review petition before the Constitutional Court through Case Number 39/PUU-XVIII/2020. The research addresses two core issues: the legal considerations of the Constitutional Court in reviewing Article 1 point 2 of the Broadcasting Law, and the juridical basis of the Court’s decision concerning the differential treatment between conventional television broadcasting and Over The Top media services from the perspective of justice. The study aims to analyze the Constitutional Court’s decision through a philosophical-juridical approach by employing John Rawls’s theory of justice and the principles of Islamic Legal Philosophy to assess the extent to which the ruling aligns with substantive justice. This research adopts a normative legal method using primary and secondary sources collected through literature review, observation, interviews, and documentation. The data were analyzed qualitatively to elaborate on the Court’s legal reasoning, the regulatory context, and the justice implications of the decision. The findings show that the Constitutional Court rejected the judicial review petition on the grounds of fundamental technical differences between conventional broadcasting and Over The Top services, thereby excluding digital platforms from the scope of the Broadcasting Law. The analytical assessment reveals that although the ruling is formally valid, it does not fully achieve substantive justice. Rawlsian evaluation demonstrates a violation of the Difference Principle due to the creation of unequal competitive conditions disadvantaging national broadcasters. Meanwhile, Islamic Legal Philosophy, through the concepts of al-maslahah and taw?zun, emphasizes the need for balanced social and moral responsibilities that are not yet addressed within the current legal framework. The implications of this study highlight the urgency of comprehensive and adaptive media law reform to respond to digital transformation. Regulatory renewal is required to ensure distributive justice, strengthen the protection of national broadcasting industries, and uphold public welfare amid the rapidly evolving internet-based media ecosystem. [Perkembangan teknologi digital melahirkan layanan media Over The Top berbasis internet yang beroperasi tanpa berada dalam rezim pengaturan penyiaran sebagaimana televisi konvensional yang diatur melalui Undang-Undang Nomor 32 Tahun 2002. Ketidakseimbangan regulasi tersebut memunculkan persoalan keadilan karena televisi konvensional menanggung kewajiban hukum yang lebih berat dibandingkan platform digital, sehingga diajukan pengujian norma melalui perkara Mahkamah Konstitusi Nomor 39/PUU-XVIII/2020. Permasalahan penelitian ini mencakup dua hal, yaitu pertimbangan hukum Mahkamah Konstitusi dalam memutus pengujian Pasal 1 angka 2 Undang-Undang Penyiaran serta dasar yuridis putusan tersebut terhadap perbedaan perlakuan antara penyiaran televisi konvensional dan media Over The Top dalam perspektif keadilan. Penelitian ini bertujuan menganalisis putusan Mahkamah Konstitusi secara filosofis-yuridis menggunakan teori keadilan John Rawls dan prinsip-prinsip Filsafat Hukum Islam untuk menilai kesesuaian putusan dengan prinsip keadilan substantif. Penelitian menggunakan metode normatif dengan sumber data primer dan sekunder, diperoleh melalui studi pustaka, observasi, wawancara, dan dokumentasi. Analisis data dilakukan secara deskriptif kualitatif untuk menguraikan argumentasi hukum, konteks regulasi, dan implikasi keadilan dalam putusan tersebut. Hasil penelitian menunjukkan bahwa Mahkamah Konstitusi menolak permohonan uji materiil atas dasar perbedaan karakteristik teknis antara penyiaran televisi dan layanan Over The Top sehingga platform digital tidak termasuk dalam cakupan Undang-Undang Penyiaran yang berlaku. Temuan analitis menunjukkan bahwa putusan tersebut, meskipun sah secara formal, belum sepenuhnya memenuhi prinsip keadilan substantif. Telaah berdasarkan teori Rawls menegaskan adanya pelanggaran terhadap prinsip perbedaan karena terciptanya ketidakseimbangan kompetisi antara pelaku penyiaran nasional dan penyedia layanan digital. Perspektif Filsafat Hukum Islam melalui konsep al-maslahah dan taw?zun mengharuskan adanya keseimbangan tanggung jawab sosial yang belum terakomodasi dalam putusan tersebut. Implikasi penelitian ini menunjukkan perlunya reformasi hukum penyiaran yang bersifat komprehensif dan adaptif terhadap transformasi digital. Pembaruan regulasi diperlukan untuk memastikan keadilan distributif, perlindungan industri penyiaran nasional, sekaligus menjaga kemaslahatan publik di tengah perkembangan ekosistem media berbasis internet.]